Preferensi Konsumen terhadap Atribut Kualitas Tiga Jenis Sayuran Indigenous di Jawa Timur, Indonesia - Yurlisa, Kartika; Dawam Maghfoer, Moch.; Aini, Nurul; Sumiya Dwi Yamika, Wiwin (Jurnal Hortikultura Indonesia, 2019)
Indigenous vegetable production is a primary source of revenue for micro-scale vegetable farmers in East Java Province. Despite the, information about consumer preference on the quality attribute of the indigenous vegetables is still lack. Thus, the study purposed to determine consumer preferences on the quality attribute of leafy greens basil, kenikir and watercress to improve the quality on the farm level. The research conducted through consumer survey in seven sites, namely Surabaya, Malang, Kediri, Madiun, Jember, Bojonegoro, Pamekasan, East Java Indonesia from July to August 2017. The site selection based on sociocultural and the composition of diverse communities. From seven sites, a total of 210 female respondents interviewed randomly. Consumer preferences on the quality attributes concluded by the method based on rank orders and analyzed with Chi-square. The experimental results showed that consumer preference for quality attributes depend on the vegetable. For basil: leaf color was light green, a large number of leaves, without a flower, medium leaf size (3.5 cm diameter), number of branches/stalk, no spicy taste, and smells stung. For kenikir: leaf color was light green, a large number of leaves, without a flower, medium smell, a large number of branches/stem, the texture of stem not fibrous, and no bitter taste. For watercress: leaf color was green, a large number of leaves, medium stem size, soft leaf, and slightly sweet flavor.Keywords: basil, consumer preference, kenikir, vegetable quality, watercress